How Much Do New Early Educators Improve Over Time? Tracking Improvement Trajectories Among Early Educators in Louisiana - Laura Bellows; Anna Shapiro; Anna J. Markowitz; Daphna Bassok (AERA Open)
We know surprisingly little about returns to experience among new teachers working with very young children, ages 2 to 5 years. This study begins to fill that gap using data on early care and education teachers working in all publicly funded, center-based settings in one state to document the relationship between teacher experience and an observational measure of teacher–child interaction quality. We used both cross-sectional data—similar to the data used in prior small studies—and longitudinal data that allowed us to track the improvement trajectories of individual teachers over a 3-year period. Our findings show considerable improvements over a 3-year period, particularly among new teachers (0.67 SD). Our longitudinal analysis also showed that, although teachers in childcare centers and Head Start began their careers with lower scores than teachers working in school-based pre-K programs, they demonstrated steeper growth trajectories.